Recognizing knowledge sharing barriers in small software development organizations - Skants, Ville (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
Knowledge sharing (KS) has become a popular topic in the era of digitalization as many organizations try to put efforts to the management of organizational knowledge in order to use it as an asset in their business. Today's business environment is characterized by increasingly high level of competition and change which has led organizations to contemplate how they can leverage the knowledge they have in their organizations. Organizational knowledge and its systematic sharing can help organizations to be more efficient in their daily work and thus gain competitive advantage over competitors. Knowledge sharing is an important topic within software development domain that is greatly knowledge intensive type of business and work. Small and medium-sized (SME) software companies that account for 70% of the Finnish software market is an interesting of target of research as their KS activities have not been studied yet comprehensively. This study researches knowledge sharing barriers and their recognition in small software development organizations. The main research question of this thesis is: What are the perceived knowledge sharing barriers in small software development organizations? First, the thesis reviews the existing literature about knowledge sharing barriers. This comprises the theoretical part of thesis introducing what knowledge, knowledge sharing and knowledge sharing barriers mean by reviewing the most significant scientific literature about the topic. Work roles in software development teams and small software development companies are addressed as well. The literature review acts as a basis for the empirical study that will be conducted through a qualitative case study by interviewing three small software development organizations. The research shows that knowledge sharing barriers in SE-sized software development organizations fall into organizational and individual issues rather than technological. Typical KS barriers e.g. lack of communication occur due to reasons that can derive from multiple levels of an organization. Based on the empirical study a framework of factors possibly creating knowledge sharing barriers is created. With the help of the framework, organizations can consider how to design and implement patterns and practices at daily work so that knowledge sharing is maximized.